The effectiveness of Nigella sativa seed extract in inhibiting Candida albicans on heat cured acrylic resin - Hanoem EH; Imam B; Kartika Purnama Pranoto (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2011)
Background: Indonesia has a variety of plants that can be used for medicines. One of the medicinal plants is Nigella sativa. Nigella sativa has been used for medicinal purposes, both as medicinal herb and as medicinal oil. It contains saponin and atsiri oils that have antifungal, antimicrobial and antibacterial effects. Nigella sativa has been suggested as denture cleansers since it can inhibit the growth of Candida albicans (C. albicans) on heat cured acrylic resin. Purpose: The aim of this research is to know the effectiveness of Nigella sativa seed extract in inhibiting the growth of C. albicans on heat cured acrylic resin. Methods: Eighteen acrylic samples were divided into three groups. Group I was control group, only contaminated with C. albicans without immersing in any solution. Group II was acrylic sample immersed in sterile aquades for one hour. Group III was acrylic sample immersed in Nigella sativa seed extract for one hour. Results: There were significant differences of C. albicans (p < 0.05) among the three groups. The number of Candida albicans was significantly higher in Group I, while that in group II was lower than that in group I, and that in group III was the lowest. Conclusion: Nigella sativa seed extract was effective in inhibiting the growth of C. albicans on heat cured acrylic resin.Latar belakang: Indonesia memiliki berbagai tanaman yang dapat dipakai sebagai obat, salah satu tanaman tersebut adalah jinten hitam (Nigella sativa). Pada beberapa negara jinten hitam telah digunakan untuk berbagai tujuan, baik sebagai obat herbal maupun sebagai minyak. kandungan jinten hitam adalah saponin dan minyak atsiri yang mempunyai efek anti jamur dan anti mikroba. Jinten hitam disarankan sebagai pilihan pembersih gigi tiruan yang dapat menghambat pertumbuhan Candida albicans (C. albicans) pada resin akrilik heat cured. Tujuan: Tujuan penelitian ini adalah mengetahui efektivitas dari ekstrak biji jinten hitam dalam menghambat pertumbuhan C. albicans pada resin akrilik heat cured. Metode: Delapan belas sampel akrilik heat cured dibagi dalam tiga kelompok, kelompok I sebagai kelompok kontrol, lempeng akrilik tanpa direndam dalam bahan apapun selama 1 jam. Kelompok perlakuan II, lempeng akrilik direndam dalam aquades steril selama 1 jam. Kelompok perlakuan III, lempeng akrilik direndam dalam ekstrak biji jinten hitam selama 1 jam. Hasil: Ada perbedaan yang bermakna dari C. albicans (p < 0,05) pada ketiga kelompok tersebut. Jumlah C. albicans lebih banyak secara bermakna pada kelompok I, pada kelompok II lebih sedikit daripada kelompok I dan kelompok III paling sedikit. Kesimpulan: Ekstrak biji jinten efektif dalam menghambat pertumbuhan C. albicans pada resin akrilik heat cured.